Pengaruh Edukasi dan Homecare Terhadap Pengetahuan, Kepatuhan, Outcome Terapi Pasien DM di Puskesmas Tebet - Arinda Utami; Siska Siska; Muhamad Syaripuddin; Numlil Khaira Rusdi (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Increasing knowledge and compliance of type 2 DM patients must be supported by pharmaceutical services by pharmacists in the form of education and homecare. This study aims to determine the effect of pharmacist services on knowledge, compliance and clinical outcomes in the form of blood glucose levels of type 2 DM patients. This study is prospective with a pretest and posttest control group design plan randomly or Randomized Controlled Trial, Respondents numbered 108 people divided into 3 groups: the control group, the education group which was given education twice using booklet media, and the education and homecare group which was given education and homecare by pharmacists twice each. The results showed that in the control group, Fasting Blood Glucose levels decreased from an average of 146.28 mg/dL to 136.89 mg/dL (p<0.05) which indicated a significant decrease. However, the increase in compliance scores from 3.94 to 4.50 (p>0.05) and knowledge scores from 59.86 to 60.72 (p>0.05) were not statistically significant. The conclusion of the study is that educational interventions, either alone or combined with homecare, significantly increased patient compliance and knowledge, although fasting blood glucose levels did not show a significant decrease